Namenwechsel. Die soziale Funktion von Vornamen im Transitionsprozess transgeschlechtlicher Personen - Schmidt-Jüngst, Miriam (2020)
This interdisciplinary study examines how transgender individuals change their names in the course of their gender transition. It reveals the enormous social significance of first names in interpersonal communication and managing gender - along with other social differences - thereby showing the close interrelationships between language, law, and society in this realm